Level of attention of the students of the Professional School of Primary and Intercultural Bilingual Education of the National University of Huancavelica - Peru (GnosisWisdom, 2022)
The research was basic and descriptive level. The general objective was to know the level of attention of the students from the I to the IX cycle of the Professional School of Primary and Intercultural Bilingual Education-Huancavelica-Peru. For this purpose, the descriptive method was used, the survey technique and the Faces Test was applied as an instrument.There was a sample of 110 students from the intervened institution. The results showed that the levels of attention of the students from the I to the IX cycle of the Professional School of Primary Education prevail: 22.5% is very low, 18.0% low, 5.6% medium-low, 36.0% medium, 9.0% medium-high, 7.9% high and 1.1% very high. This indicates that students in their daily work and learning activities are presenting weaknesses in their attention and concentration, thereby causing low and medium satisfactory response to cognitive concerns and questions.
Keywords: Attention; memory